Seleção em população base de pimenteiras ornamentais (Capsicum annuum L.) - Lima, Jose Ayron Moraes de (2018)
The peppers plants of the genus Capsicum are part of the heritage of Brazilian biodiversity, which differs as to the type, color, size, flavor, and poignancy in various marketed cultivars. All information regarding the variability of a germplasm collection serves to increase the efficiency of the species improvement works, to refer to the various accesses of a collection, by means of ornamental interest characteristics. The aim of this study was to characterize and select plants with ornamental potential and resistant to pathogens in generation F2. The experiment was conducted in a greenhouse of the Plant Biotechnology Laboratory of the Center of Agrarian Sciences (CCA) of the Federal University of Paraíba (UFPB). The treatments consisted of 354 progenies, an F2 generation of ornamental peppers (Capsicum annuum L), belonging to the Bank of germplasm of UFPB, derived from the controlled self- fertilization of F1 and obtained from the crossing between the parents UFPB390 X UFPB137, plants grown in vessels of 900 mL filled with commercial substrate. As they reached adulthood, genotypes were characterized according to the descriptors for Capscicum suggested by IPGRI, (1995). 20 quantitative characters and 4 qualitative in ornamental peppers were evaluated. Leaves identified from an optical microscope using the illustrated descriptor of imperfect fungus. For genetic divergence analysis, Tocher's grouping method was used, based on the standardized Euclidean distance. Analyses were carried out for the quantitative and qualitative data separately and also for the data together. In addition, the relative importance of the characteristics evaluated for genetic divergence was calculated using SINGH's Methodology (1981). All analyses were performed using the computational Genes program . There was variability among genotypes for the evaluated characters. The variability between genotypes was higher for qualitative characters related to disease resistance. It is possible to select individual plants for opening lines in Generation F3. 7 plants; 7; 15; 50; 69; 120; 155; 157; 196; 314; 326; 331; 347 should be selected for not presenting symptoms of fungi diseases